2005
DOI: 10.1111/j.0730-7659.2005.0347a.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies in Breastfeeding: Problem‐Solving Skills & Strategies

Abstract: 195 pp, $34.95, pb With the explosion of knowledge about breastfeeding management over the last two decades, the help that mothers need to breastfeed their babies should be readily available. Happily, for many mothers this is the case. But others aren't helped as effectively as they ought to be because their health care providers don't know how to counsel well. This book is designed especially for breastfeeding specialists who are not "natural" counselors or who don't (yet) know how to transmit their fund o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…At present in Australia, second-line strategies are often controlled by policies at birthing facilities [ 42 , 43 ] and opportunities for women to engage in informed decision making about such strategies may be limited. There is some discussion in recent literature that control of breastfeeding should be ‘handed back’ to women [ 41 , 44 , 45 ]. Evidence of the success of this approach has been provided by Wan et al [ 46 ], who found increased satisfaction in woman-centred postpartum care rather than task-centred postpartum care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present in Australia, second-line strategies are often controlled by policies at birthing facilities [ 42 , 43 ] and opportunities for women to engage in informed decision making about such strategies may be limited. There is some discussion in recent literature that control of breastfeeding should be ‘handed back’ to women [ 41 , 44 , 45 ]. Evidence of the success of this approach has been provided by Wan et al [ 46 ], who found increased satisfaction in woman-centred postpartum care rather than task-centred postpartum care.…”
Section: Discussionmentioning
confidence: 99%
“…Choice of second-line strategies by the woman should be based on her own values and beliefs (which form BFSE via vicarious learning and verbal/social persuasion), establishing a continuance of woman-centred care beyond birth. Where women have knowledge deficits, a continuity of care model facilitates education based on midwives prior knowledge of the woman [ 45 ].…”
Section: Discussionmentioning
confidence: 99%